2009
DOI: 10.1007/s12529-009-9071-3
|View full text |Cite
|
Sign up to set email alerts
|

Low Goal Ownership Predicts Drop-out from a Weight Intervention Study in Overweight Patients with Type 2 Diabetes

Abstract: BackgroundDrop-out is a major problem in weight loss studies. Although previous attrition research has examined some predictors of drop-out, theoretically grounded research on psychological predictors of drop-out from weight interventions has been lacking.PurposeTo examine psychological predictors of drop-out from a weight reduction study in diabetes type 2 patients.MethodA clinical trial was conducted with 101 overweight/obese (body mass index >27) diabetes type 2 patients. Patients were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 27 publications
2
54
0
2
Order By: Relevance
“…For example, studies using newspaper advertisements to recruit reported attrition rates from 18 to 54% [13,17,18,23] and those relying on medical professional referral reported attrition rates from 23 to 49% [11,24]. The few studies assessing readiness to change reported inconsistent results [12,[22][23][24][25]. Length of treatment did not appear to be related to attrition for example studies of 6-month [21,26] and 24-month [27,28] duration reported similar attrition rates.…”
Section: Defining Attrition In Weight-loss Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, studies using newspaper advertisements to recruit reported attrition rates from 18 to 54% [13,17,18,23] and those relying on medical professional referral reported attrition rates from 23 to 49% [11,24]. The few studies assessing readiness to change reported inconsistent results [12,[22][23][24][25]. Length of treatment did not appear to be related to attrition for example studies of 6-month [21,26] and 24-month [27,28] duration reported similar attrition rates.…”
Section: Defining Attrition In Weight-loss Interventionsmentioning
confidence: 99%
“…For example, some studies have found gender to be non-significant in predicting drop-out [25,44], while others have found female gender [28,45] and male gender to be predictive of attrition [46]. Similarly, some studies have found BMI to be non-significant in predicting drop-out [47,48], while others have found lower BMI [49,50] or greater BMI [51,52] to be significant predictors of attrition.…”
Section: Pre-treatment Predictors Of Attritionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Aunque existe una gran variedad de tratamientos para lograr el objetivo de bajar de peso de manera significativa y duradera en los pacientes con obesidad severa, las tasas de abandono de las mismas se encuentran entre el 40% y 80%. 10,11 El abandono o deserción en el tratamiento contribuye a mantener e incrementar los riesgos de aparición de enfermedades crónico-degenerativas asociadas a la obesidad 12 y de las patologías psicológicas y psiquiátricas. Se ha encontrado en la literatura médica que los pacientes con obesidad que desertan del tratamiento podrían tener algunos factores psicológicos y/o psiquiátricos que los caracterizan.…”
Section: -7unclassified